Analysis of the Erosion Characteristics and Microstructural Effects of 1.17% Carbon Hyper-eutectoid Steel - Mani P.C.; Harsha A.P.; Manna R.; Biswas S. (My University, 2025)
This study presents the erosion behaviour of hyper-eutectoid steel against alumina as an erodent. 1.17% carbon hyper-eutectoid steel samples were heat treated to get pearlitic and martensitic microstructure to analyze the erosion resistance for their microstructures. The erosion tests were conducted on normalized and hardened steel using alumina erodent. The impact angles ranged from 15° to 90°, while the velocities varied between 40 to 90 m/s. The steady-state erosion rate was then measured. The erosion behaviour was analyzed with the power law model represented by E=kvn. The erosion resistance of normalized steel was superior to that of hardened steel under high-impact angles and high velocities. The highest erosion rate for normalized steel was 30° impact angle, while for hardened steel it was 60° to 90°. The erosion resistance of normalized steel was augmented with an escalation in hardness, but the converse trend was observed in the case of hardened steel. Scanning electron microscopy (SEM) was conducted to get insight into the various erosion mechanisms. Normalized steel erosion at low-impact angles is primarily characterized by ploughing with lips and diminishes as the hardness of the steel increases. Conversely, at high-impact angles, erosion occurs through cutting, crater formation, splashing of materials, and the embedding of erodent particles, and exhibited an upward trend as the hardness level increased. Erosion of hardened steel was observed to transpire at low-impact angles, resulting in a reduced occurrence of microchipping. Conversely, at higher-impact angles, erodent becomes entrenched inside the material, forming craters and pits by the splashing of material. © The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2024.